Finite Element Analysis Based on Virtual Material and Experimental of Vacuum Chamber. Issue 3 (April 2021) - Fu, Yongling; Wang, Zeqi; Li, Wanguo
Abstract: Electron beam imaging system plays an important role in chip defect detection, so optimizing its dynamic performance is crucial. To understand the vibration characteristics of the electron beam imaging system, a reasonable finite element model is established. The simulation results show that the natural frequencies of the model adding virtual material layer are more accurate than bounded, but the local mode caused by the virtual material layer needs to be eliminated. The error of this method is within 10%, which verifies the accuracy of virtual materials in large assemblies. Our research promotes the development of the chip inspection technology.